Bridge over troubled waters: understanding the synthetic and biological identities of engineered nanomaterials. (17th January 2013) - Fadeel, Bengt; Feliu, Neus; Vogt, Carmen; Abdelmonem, Abuelmagd M.; Parak, Wolfgang J.
Abstract: Engineered nanomaterials offer exciting opportunities for 'smart' drug delivery and in vivo imaging of disease processes, as well as in regenerative medicine. The ability to manipulate matter at the nanoscale enables many new properties that are both desirable and exploitable, but the same properties could also give rise to unexpected toxicities that may adversely affect human health. Understanding the physicochemical properties that drive toxicological outcomes is a formidable challenge as it is not trivial to separate and, hence, to pinpoint individual material characteristics of nanomaterials. In addition, nanomaterials that interact with biological systems are likely to acquire a surface corona of biomolecules that may dictate their biological behavior. Indeed, we propose that it is the combination of material‐intrinsic properties (the 'synthetic identity') and context‐dependent properties determined, in part, by the bio‐corona of a given biological compartment (the 'biological identity') that will determine the interactions of engineered nanomaterials with cells and tissues and subsequent outcomes. The delineation of these entwined 'identities' of engineered nanomaterials constitutes the bridge between nanotoxicological research and nanomedicine. WIREs Nanomed Nanobiotechnol 2013, 5:111–129. doi: 10.1002/wnan.1206 This article is categorized under: Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials